Upper-stratospheric temperature trends: new results from the Optical Spectrograph and InfraRed Imager System (OSIRIS) - K. Dubé; S. Tegtmeier; A. Bourassa; D. Zawada; D. Degenstein; W. Randel; S. Davis; M. Schwartz; N. Livesey; A. Smith (Atmospheric Chemistry and Physics)
Temperature trends in the upper stratosphere, particularly above ∼ 45 km, are difficult to quantify due to a lack of observational data with high vertical resolution in this region that span multiple decades. The recent v7.3 upper-stratospheric (35–60 km) temperature data product from the Optical Spectrograph and InfraRed Imager System (OSIRIS) includes over 22 years of observations that can be used to estimate temperature trends. The trends in OSIRIS temperatures over 2005–2021 are compared to those from two other satellite limb instruments: Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) and Microwave Limb Sounder (MLS). We find that the upper stratosphere cooled by ∼ 0.5 to 1 K per decade during this period. Results from the three instruments are generally in agreement. By merging the OSIRIS observations with those from channel 3 of the Stratospheric Sounding Unit (SSU), we find that the stratosphere cooled at a rate of approximately −0.6 K per decade between 1979 and 2021 near 45 km, in agreement with earlier results based on SSU and MLS. The similarity between OSIRIS temperature trends and those from other records improves confidence in observed upper-stratospheric temperature changes over the last several decades.